Polymerization of Substituted Acetylenes Using Well‐Defined Rhodium Complex Catalyst. Chirality Transfer and Amplification in Chiral‐Chiral Block and Random Copolymers. Issue 9 (4th September 2019) - Goto, Masahide; Nito, Ayaka; Miyagi, Yu; Sanda, Fumio
Abstract : Inside Front Cover : In article number1900275, Fumio Sanda and coworkers synthesize block and random copolymers by the polymerization ofl ‐ andd ‐valine‐derived phenylacetylene monomers using a well‐defined rhodium complex catalyst. The authors demonstrate the chirality transfer and amplification in the block and random copolymers, respectively. The transmitted chirality of the block copolymers is kept memorized upon changing temperature.